2016
DOI: 10.1155/2016/1458548
|View full text |Cite
|
Sign up to set email alerts
|

Valproate Induced Hypertensive Urgency

Abstract: Valproate is a medication used in the treatment of seizures, bipolar disorder, migraines, and behavioral problems. Here we present a case of an 8-year-old boy who presented with hypertensive urgency after initiation of valproate. Primary treatment of his hypertension was ineffective. Blood pressure stabilization was achieved following discontinuation of valproate. Clinicians should be aware of the risk of developing hypertensive urgency with administration of valproate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…With mood stabilizers like lithium, animal models demonstrated antihypertensive effects [122] through its similar renal effects in humans [123]. Valproate, on the other hand, has been associated with hypertension in 1–5% of patients, [124] including a case report of a valproate-associated hypertensive urgency in an 8 year old child which resolved with discontinuation of the medication [125].…”
Section: Introductionmentioning
confidence: 99%
“…With mood stabilizers like lithium, animal models demonstrated antihypertensive effects [122] through its similar renal effects in humans [123]. Valproate, on the other hand, has been associated with hypertension in 1–5% of patients, [124] including a case report of a valproate-associated hypertensive urgency in an 8 year old child which resolved with discontinuation of the medication [125].…”
Section: Introductionmentioning
confidence: 99%
“…52 Mixed responses in BP are reported in human patients after valproate administration. 53,54 The effect of other HDACis, such as vorinostat, sodium butyrate, and entinostat, on hypertensive rodent models is discussed in the Supplemental Material.…”
Section: Reviewmentioning
confidence: 99%
“…Valproic acid has been shown to lower blood pressure in spontaneusly hypertensive rats Cardinale et al [13] and prevented high fat diet-induced hypertension (Choi, et al [14]). On the other hand, it has been reported that one of the side effects of taking valproate is increased blood pressure and high heart rate (Sivananthan, et al [15]). Due to the contradictory results of the effect of sodium valproate (VPA) on blood pressure; In this study, the role of VPA on the hypertension of epileptic rats was investigated by the kindling method (Figure 1).…”
Section: Introductionmentioning
confidence: 99%